MIMO wireless communications - Biglieri, Ezio (Cambridge University Press, 2007)
Detailed introduction to the analysis and design of MIMO wireless systems from a team of leading experts, blending theoretical analysis with physical insights, and highlighting key design challenges. Suitable as a textbook for advanced courses on wireless communications. Will also appeal to researchers and practitioners working on MIMO wireless systems.
Keywords: MIMO systems.; elektronické knihy; electronic books